Analysis of Online Gaming Enthusiast Parents' Preferences in Games Selection as an Optimization for Early Childhood Social Emotional Development - Putri Kartika Wijayanti (BELIA Early Childhood Education Papers, 2026)
Online games are a form of digital entertainment widely favored by young children. Selecting games without considering their educational value and social emotional impact can create challenges for children’s development. This study aims to analyze the preferences of online game–enthusiast parents in choosing games to optimize their children’s social emotional development and to understand the effects of online games on early childhood social emotional growth. This research employed a qualitative case-study approach involving three online game enthusiast parents in Semarang City who have children aged 5–6 years. Data were collected through observation, interviews, and documentation. The findings show that parents have distinct preferences in selecting games for their children, including their own personal interests, potential skill development, play duration, game reputation, guidance, safety, and age-appropriate content. In addition, children’s gameplay produced effects such as enhanced social interaction, cooperation, emotional regulation, and the emergence of positive emotions. The study recommends that parents be more actively involved in guiding and directing their children to ensure optimal socio-emotional development.